Preparation method of metal-doped cobalt-based dynamic catalyst and application of metal-doped cobalt-based dynamic catalyst in electrosynthesis of ammonia
The preparation of metal-doped cobalt-based dynamic catalysts by ion exchange and reducing atmosphere calcination has solved the problems of low catalyst activity and easy corrosion, and achieved efficient and stable electro-synthesis ammonia reaction, with better performance than existing catalysts.
Patent Information
- Application Number
- CN202411792687.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-14
AI Technical Summary
In the existing electrocatalytic nitrate reduction and synthesis of ammonia, the catalyst has low activity and is prone to corrosion, resulting in poor reaction selectivity and low stability.
The metal-doped cobalt-based dynamic catalyst is prepared by ion exchange and reducing atmosphere calcining. The catalyst has self-supporting characteristics and can be used as an electrode during the electro-synthesis of ammonia to regulate the reconstruction process of the cobalt-based catalyst and achieve dynamic equilibrium between cobalt hydroxide and metal cobalt.
It significantly improves the activity and stability of the catalyst, improves the selectivity and ammonia production rate of electrosynthesis ammonia reaction, and has better performance than most electrosynthesis ammonia catalysts.
Smart Images

Figure CN119615255A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a method for preparing a metal-doped cobalt-based dynamic catalyst. The present invention also relates to application of the metal-doped cobalt-based dynamic catalyst in electrosynthesis of ammonia. Background Art
[0002] As one of the most important chemical products in the world, ammonia has an annual output of more than 200 million tons and has important application value in agriculture, chemical industry, energy and other fields. In agriculture, more than 80% of the total ammonia output is used for the production of fertilizers, providing sufficient food supply for the growing population in the world. In addition, ammonia is also a basic raw material for the production of important industrial chemicals such as plastics, explosives, pharmaceuticals, synthetic fibers and resins. As a hydrogen energy carrier and a carbon-free clean fuel, ammonia also has unique advantages in storage and transportation.
[0003] At present, the traditional Haber-Bosch method is mainly used for large-scale industrial ammonia synthesis. This process includes two stages: the first stage is the hydrogen production stage, which is mainly produced by methane reforming. A large amount of carbon dioxide will be produced during the production process; the second stage is the synthesis of ammonia by the reaction of nitrogen and hydrogen. This process requires harsh reaction conditions of high temperature (300-500°C) and high pressure (150-200atm). The reaction energy consumption exceeds 1% of the global total energy consumption, which imposes a serious burden on the global energy supply. In the process of methane reforming to produce hydrogen, the consumption of natural gas accounts for about 3% to 5% of the global total natural gas consumption, and the carbon dioxide emitted accounts for about 1.2% of the total global carbon dioxide emissions. The greenhouse gases produced have exacerbated the negative impact of the reaction process on the global ecological environment. Therefore, the development of a new type of ammonia synthesis process with low energy consumption and clean and environmental protection is of great significance to the sustainable development of human society.
[0004] The electro-synthetic ammonia process can achieve controllable synthesis of ammonia at room temperature and pressure by changing the applied potential. Its raw materials (nitrogen and water) are easy to obtain, energy consumption is low, and the equipment is simple, which is expected to achieve clean production of ammonia. However, the chemical properties of nitrogen are very stable, and the N≡N bond energy is very high (941kJ mol -1 ), so it is extremely difficult to synthesize ammonia by electrocatalytic nitrogen reduction at room temperature and pressure. In comparison, nitrate has a lower bond energy (204kJ mol -1 ) is easier to activate and is widely found in agricultural sewage and industrial wastewater. Therefore, electrocatalytic nitrate reduction to synthesize ammonia can convert harmful nitrogen oxides in wastewater into high-value-added ammonia, synergistically achieving wastewater denitrification and clean ammonia production.
[0005] However, the electrocatalytic reduction of nitrate to synthesize ammonia involves multiple elementary reactions with many reaction by-products, resulting in poor selectivity for the target product. In addition, the catalyst is susceptible to corrosion by the electrolyte during the reaction, and the structure and phase of the catalyst undergo irreversible changes, leading to the deactivation of the catalyst and reduced stability of the electrosynthesized ammonia. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defect of low catalyst activity in the prior art, thereby providing a method for preparing a metal-doped cobalt-based dynamic catalyst, in which the metal-doped cobalt-based catalyst is prepared by ion exchange and calcination in a reducing atmosphere. The catalyst has self-supporting characteristics, is highly active, and can be directly used as an electrode in the process of electrosynthesis of ammonia, thereby greatly improving the stability of the reaction.
[0007] Furthermore, the present invention also provides a method for electrosynthesizing ammonia using the above-mentioned metal-doped cobalt-based catalyst. The metal doping of the present invention is beneficial to regulating the reconstruction process of the cobalt-based catalyst during the reaction process, achieving a dynamic balance between cobalt hydroxide and metallic cobalt, and realizing efficient and stable electrosynthesis of ammonia.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] A method for preparing a metal-doped cobalt-based dynamic catalyst comprises the following steps:
[0010] S1. Preparation of cobalt-based metal organic framework supported by metal foam:
[0011] Mixing dimethylimidazole and cobalt nitrate solution, then immersing the surface pretreated foam metal support in the mixed solution, standing for 5 to 25 hours, rinsing, and then vacuum drying for 12 to 48 hours to obtain a foam metal-supported cobalt-based metal organic framework;
[0012] S2. Preparation of metal-doped cobalt-based metal-organic frameworks
[0013] The cobalt-based metal organic framework supported by the metal foam prepared in step S1 is placed in a precursor metal solution to undergo an ion exchange reaction, and stirred for 1 to 5 hours, so that the metal ions in the precursor metal solution partially replace the cobalt ions to obtain a metal-doped cobalt-based metal organic framework supported by the metal foam;
[0014] S3, placing the metal-doped cobalt-based metal organic framework supported by the metal foam prepared in step S2 in a tube furnace, introducing a protective gas, and calcining at a temperature of 400 to 600° C. for 0.5 to 2 hours to obtain a metal-doped cobalt oxide / metal cobalt composite material catalyst supported by the metal foam;
[0015] S4. Reconstruction of metal-doped cobalt oxide / metallic cobalt composite catalyst supported by metal foam
[0016] At a reduction potential of -0.1V to -0.7V and a nitrate ion concentration of 0.01 to 0.5M, the catalyst undergoes dynamic reconstruction to form a metal-doped cobalt-based dynamic catalyst.
[0017] The foam metal is foam nickel, foam cobalt or foam iron, and the pore diameter of the foam metal is 0.2-0.6 mm, preferably 0.4 mm.
[0018] In the step S1, the molar ratio of dimethylimidazole to the cobalt nitrate solution is 4:1 to 16:1.
[0019] The method for pretreating the surface of the foam metal carrier is to ultrasonically treat the foam metal carrier in a hydrochloric acid solution to remove surface oxides.
[0020] The rinsing is performed by rinsing with deionized water 2-4 times.
[0021] The precursor metal solution is one of sodium chromate, sodium molybdate or tungstic acid solution.
[0022] The concentration of the precursor metal solution is 2-10 mM, and the mass fraction of metal ions in the metal-doped cobalt-based metal organic framework is 6-16 wt %.
[0023] The protective gas introduced in step S3 is a mixed gas of argon and hydrogen.
[0024] In step S4, the nitrate ions come from one of potassium nitrate, sodium nitrate or lithium nitrate or a mixture of several nitrates thereof.
[0025] A metal-doped cobalt-based dynamic catalyst prepared by the method.
[0026] An application of the metal-doped cobalt-based dynamic catalyst in the electro-synthesis of ammonia reaction.
[0027] The technical solution of the present invention has the following advantages:
[0028] The metal-doped cobalt-based dynamic catalyst prepared by the present invention is specifically a chromium-doped cobalt-based dynamic catalyst, a molybdenum-doped cobalt-based dynamic catalyst or a tungsten-doped cobalt-based dynamic catalyst. In the process of synthesizing ammonia, cobalt oxide is first reduced to metallic cobalt, and metallic cobalt undergoes a spontaneous oxidation-reduction reaction with nitrate ions to obtain cobalt hydroxide and nitrite ions, while cobalt hydroxide can obtain electrons to form metallic cobalt. In this process, chromium doping can regulate the reconstruction process of the cobalt-based catalyst during the electro-synthetic ammonia reaction, achieve a dynamic balance between cobalt hydroxide and metallic cobalt, and improve the electro-synthetic ammonia reaction activity and stability.
[0029] Compared with the existing electro-synthetic ammonia catalyst, the metal-doped cobalt-based dynamic catalyst prepared in the present invention has unique advantages in interfacial water activation and nitrogen oxide conversion, and shows excellent application prospects.
[0030] The different components of the metal-doped cobalt-based dynamic catalyst have a significant synergistic effect:
[0031] On the one hand, the metal-doped cobalt hydroxide component can form hydrogen bond interactions with interfacial water molecules, thereby destroying the network configuration between water molecules and promoting the dissociation of interfacial water molecules on the catalyst surface, thereby providing more active hydrogen for the hydrogenation reaction step of synthetic ammonia;
[0032] On the other hand, the metal cobalt component is conducive to the adsorption and activation of nitrate ions, and uses the active hydrogen generated by water dissociation to hydrogenate and convert nitrate ions, thereby promoting the generation of the target product ammonia. The chromium-doped cobalt-based dynamic catalyst prepared by the present invention can achieve ammonia production Faraday efficiency of more than 95% in the voltage range of -0.1V to -0.7V (relative to the reversible hydrogen electrode potential), and the ammonia production Faraday efficiency can reach up to 97.36%, and the ammonia production rate can reach up to 58.92mg h -1 cm -2 The maximum current density of the ammonia production part is 765.42 mA cm -2 , performance is better than most electro-ammonia synthesis catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 Schematic diagram of the preparation principle of the chromium-doped cobalt-based dynamic catalyst in Example 1;
[0035] Figure 2 This is the dynamic reconstruction process of the chromium-doped cobalt-based catalyst of the present invention;
[0036] Figure 3 This is a transmission electron microscope characterization image of chromium-doped cobalt-based catalyst;
[0037] Figure 4 This is the electrochemical in-situ X-ray diffraction spectrum of chromium-doped cobalt-based catalyst;
[0038] Figure 5 Faradaic efficiency of ammonia production of chromium-doped cobalt-based catalysts at different potentials;
[0039] Figure 6 Ammonia production rates of Example 1, Comparative Example 1 and Comparative Example 2 at different potentials
[0040] Figure 7 Example 1 Changes in nitrogen content during continuous electrolysis of nitric acid in simulated wastewater by chromium-doped cobalt-based catalysts;
[0041] Figure 8 This is a comparison of scanning electron microscope images of the chromium-doped cobalt-based catalyst before and after reconstruction. DETAILED DESCRIPTION
[0042] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The present invention provides a method for preparing a metal-doped cobalt-based dynamic catalyst, comprising the following steps:
[0044] S1. Preparation of cobalt-based metal organic framework supported by metal foam:
[0045] The nickel foam was ultrasonically treated in a hydrochloric acid solution to remove surface oxides;
[0046] A solution of dimethylimidazole and cobalt nitrate solution in a molar ratio of 4:1 to 16:1 is mixed, and the surface pretreated foam metal carrier is immersed in the mixed solution, and then rinsed with deionized water for 2-4 times after standing for 5 to 25 hours, and then vacuum dried for 12 to 48 hours to obtain a cobalt-based metal organic framework supported by the foam metal; the dimethylimidazole is used as an organic ligand to coordinate with cobalt nitrate to synthesize the metal organic framework.
[0047] S2. Preparation of metal-doped cobalt-based metal-organic frameworks
[0048] A precursor metal solution is prepared with a concentration of 2 to 10 mM, wherein the precursor metal solution is one of sodium chromate solution, sodium molybdate or sodium tungstate;
[0049] The cobalt-based metal organic framework supported by the metal foam prepared in S1 is placed in a precursor metal solution, stirred for 1 to 5 hours, and an ion exchange reaction occurs, whereby the metal ions in the precursor metal solution partially replace the cobalt ions to obtain a metal-doped cobalt-based metal organic framework supported by the metal foam;
[0050] S3, placing the metal-doped cobalt-based metal organic framework supported by the metal foam prepared in step S2 in a tube furnace, introducing a mixed gas of argon and hydrogen as protective gas, and calcining at a temperature of 400-600° C. for 0.5-2 hours to obtain a metal-doped cobalt oxide / metal cobalt composite catalyst supported by the metal foam.
[0051] S4. Reconstruction of metal-doped cobalt oxide / metallic cobalt composite catalyst supported by metal foam
[0052] Under the reduction potential and nitrate ion concentration, the catalyst undergoes dynamic reconstruction, e.g. Figure 8 As shown, Figure 8 (a) SEM image of Cr-doped Co-based catalyst before reconstruction. Figure 8 (b) SEM image of the chromium-doped cobalt-based catalyst after reconstruction, forming a metal-doped cobalt-based dynamic catalyst.
[0053] The present invention ultrasonically treats the foam metal in a hydrochloric acid solution to remove surface oxides. In the present invention, the foam metal is foam nickel, foam cobalt or foam iron, and the thickness of the foam metal is preferably 0.5-1.5 mm, preferably 1.0 mm; the pore size is preferably 0.2-0.6 mm, more preferably 0.4 mm. The present invention has no special restrictions on the size of the foam metal, which can be set as needed. In the present invention, the concentration of hydrochloric acid is preferably 10-40% (volume fraction), more preferably 25%. The present invention has no special restrictions on the power of ultrasonic treatment, as long as the oxides on the surface of the foam metal can be removed. The ultrasonic treatment time is preferably 10-20 minutes, more preferably 15 minutes. In the present invention, the water used for water washing is preferably deionized water.
[0054] After the metal foam is pretreated with hydrochloric acid, it is placed in a mixed solution of dimethylimidazole and cobalt nitrate, and after standing for a period of time, it is washed with deionized water and vacuum dried to obtain a cobalt-based metal organic framework loaded with the metal foam. In the present invention, the molar ratio of the methylimidazole solution to the cobalt nitrate solution is preferably 4:1 to 16:1, and more preferably 8:1. The standing time of the metal foam in the mixed solution of methylimidazole and cobalt nitrate is preferably 5 to 25 hours, and more preferably 15 hours. The water used for the water washing is preferably deionized water. The vacuum drying temperature is preferably 40 to 80°C, and more preferably 60°C. The vacuum drying time is preferably 12 to 48 hours, and more preferably 24 hours.
[0055] The cobalt-based metal organic framework supported by the foam metal is placed in a sodium chromate solution of a certain concentration, an ion exchange reaction is carried out, and after stirring for 1 to 5 hours, the chromium-doped cobalt-based metal organic framework supported by the foam metal is obtained by washing with deionized water and vacuum drying. In the present invention, the concentration of the sodium chromate solution is preferably 2 to 10 mM, more preferably 6 mM. The stirring rate is preferably 400 to 800 rpm, more preferably 600 rpm. The stirring time is preferably 1 to 5 hours, more preferably 2.5 hours. The water used for the water washing is preferably deionized water. The vacuum drying temperature is preferably 40 to 80°C, more preferably 60°C. The vacuum drying time is preferably 12 to 48 hours, more preferably 24 hours.
[0056] The metal-doped cobalt-based metal organic framework supported by the foam metal is placed in a tube furnace, a mixed gas of argon and hydrogen is introduced, and the foam metal-doped cobalt oxide / metal cobalt composite material is obtained after calcination. In the present invention, the hydrogen content in the mixed gas is preferably 1-10%, more preferably 5%. The calcination temperature is preferably 400-600° C., more preferably 500° C. The calcination time is preferably 0.5-2 hours, more preferably 1 hour.
[0057] Under certain reduction potential and nitrate ion concentration, the chromium-doped cobalt oxide / metallic cobalt composite material supported by the foam metal undergoes dynamic reconstruction to form a chromium-doped cobalt-based dynamic catalyst. The reduction potential is preferably -0.1V to -0.7V (relative to the reversible hydrogen electrode potential), more preferably -0.4V (relative to the reversible hydrogen electrode potential). The nitrate ion concentration is preferably 0.01 to 0.5M, more preferably 0.1M.
[0058] Example 1
[0059] A method for preparing a metal-doped cobalt-based dynamic catalyst comprises the following steps:
[0060] S1. Preparation of cobalt-based metal organic framework supported by nickel foam:
[0061] The nickel foam with a thickness of 1.0 mm and a pore size of 0.4 mm was cut into a size of 3 cm × 3 cm, immersed in a hydrochloric acid solution with a volume concentration of 25%, ultrasonically treated for 15 minutes, and washed with deionized water to remove surface oxides;
[0062] A solution of dimethylimidazole and cobalt nitrate solution in a molar ratio of 8:1 was mixed, and the surface pretreated nickel foam support was immersed in the mixed solution. After standing for 15 hours, it was rinsed twice with deionized water and vacuum dried at 60°C for 24 hours to obtain a cobalt-based metal organic framework supported by nickel foam.
[0063] S2. Preparation of metal-doped cobalt-based metal-organic frameworks
[0064] Prepare a 6 mM sodium chromate solution.
[0065] The cobalt-based metal organic framework supported by nickel foam prepared by S1 was placed in a 6 mM sodium chromate solution for ion exchange reaction with a stirring rate of 600 rpm for 2.5 hours. It was washed with deionized water and vacuum dried at 60°C for 24 hours to obtain a chromium-doped cobalt-based metal organic framework supported by nickel foam.
[0066] S3. The chromium-doped cobalt-based metal organic framework supported by nickel foam prepared in step S2 is placed in a tubular furnace, a mixed gas of argon and hydrogen (hydrogen content 5%) is introduced, and calcined at 500° C. for 1 hour to obtain a chromium-doped cobalt oxide / metal cobalt composite material supported by nickel foam.
[0067] S4. Reconstruction of chromium-doped cobalt oxide / metallic cobalt composite catalyst supported by nickel foam
[0068] At a reduction potential of -0.4 V (relative to the reversible hydrogen electrode potential) and a nitrate (from potassium nitrate) ion concentration of 0.1 M, the chromium-doped cobalt oxide / metallic cobalt composite material supported on nickel foam undergoes dynamic reconstruction to form a nickel foam-supported chromium-doped cobalt-based dynamic catalyst.
[0069] Example 2
[0070] The molybdenum-doped cobalt-based dynamic catalyst was prepared according to the method of Example 1, except that a 6 mM sodium molybdate solution was used in the ion exchange reaction step.
[0071] Example 3
[0072] The tungsten-doped cobalt-based dynamic catalyst was prepared according to the method of Example 1, except that a 6 mM sodium tungstate solution was used in the ion exchange reaction step.
[0073] The schematic diagram of the principle of the chromium-doped cobalt-based dynamic catalyst prepared according to the method of the present invention is as follows Figure 1 The present invention first grows a cobalt-based metal organic framework with a nanosheet array morphology on a nickel foam substrate, and then uses an ion exchange reaction to replace the sites of cobalt ions in the cobalt-based metal organic framework with chromium ions, and obtains a chromium-doped cobalt oxide / metal cobalt composite material supported by nickel foam after calcination. The dynamic reconstruction process of chromium-doped cobalt-based catalyst is shown in FIG. Figure 2 As shown, cobalt oxide is first reduced to metallic cobalt (reaction formula (1)), and metallic cobalt undergoes a spontaneous redox reaction with nitrate ions to obtain cobalt hydroxide and nitrite ions (reaction formula (2)), while cobalt hydroxide can gain electrons to form metallic cobalt (reaction formula (3)). In this process, chromium doping can regulate the reconstruction process of cobalt-based catalysts during the electro-ammonia synthesis reaction, achieve a dynamic balance between cobalt hydroxide and metallic cobalt, and improve the activity and stability of the electro-ammonia synthesis reaction.
[0074] CoO+2e - +H2O→Co+2OH - (1)
[0075] Co+NO3 - +H2O→Co(OH)2+NO2 - (2)
[0076] Co(OH)2+2e - →Co+2OH - (3)
[0077] like Figure 3 As shown, the chromium-doped cobalt-based catalyst prepared in Example 1 was characterized by transmission electron microscopy. Figure 3 (a) is a low-magnification transmission electron microscopy image. Figure 3 (b) is a high-magnification transmission electron microscope image. Figure 3 (c) is the Fourier transform and inverse Fourier transform diagram, Figure 3 (d) is a dark field emission scanning transmission electron microscopy image. Figure 3 (e) and Figure 3 (f) Distribution diagrams of cobalt (Co) and chromium (Cr) elements, respectively. Transmission electron microscopy characterization shows that the chromium-doped cobalt-based catalyst mainly presents a nanoparticle morphology structure, and the phase components are metal Co and CoO, and the Cr doping element is uniformly distributed.
[0078] The chromium-doped cobalt-based catalyst prepared in Example 1 was characterized by electrochemical in-situ X-ray diffraction spectroscopy. Figure 4 As shown in the figure, when a negative potential is applied, the CoO diffraction peak disappears, the diffraction peak of metal Co still exists, and the diffraction peak of Co(OH)2 appears; as the applied potential shifts negatively, the diffraction peak of Co(OH)2 gradually increases, while the diffraction peak of metal Co gradually weakens; when the applied potential reaches -0.4V, as the potential shifts negatively, the diffraction peak intensity of Co(OH)2 and metal Co does not change significantly, indicating that Co(OH)2 and metal Co have reached a dynamic balance. Therefore, Cr doping is beneficial to regulating the reconstruction process of Co-based catalysts and achieving a dynamic balance between Co(OH)2 and metal Co.
[0079] The chromium-doped cobalt-based catalyst prepared in Example 1 was tested for its performance in producing ammonia by electrochemical nitric acid reduction. Figure 5 The chromium-doped cobalt-based catalyst prepared in Example 1 has a Faraday efficiency for ammonia production at different potentials. Within the voltage range of -0.1 V to -0.7 V (relative to the reversible hydrogen electrode potential), it can achieve a Faraday efficiency for ammonia production of more than 95%, and the highest Faraday efficiency for ammonia production can reach 97.36%. Figure 6The ammonia production rates of the chromium-doped cobalt-based catalyst prepared in Example 1, the molybdenum-doped cobalt-based catalyst prepared in Example 2, and the tungsten-doped cobalt-based catalyst prepared in Example 3 at different potentials. Chromium doping can significantly increase the ammonia production rate of the cobalt-based catalyst. The ammonia production rate of the chromium-doped cobalt-based catalyst can reach up to 58.92 mgh. -1 cm -2 . Figure 7 The nitrogen content of the chromium-doped cobalt-based catalyst prepared in Example 1 during the continuous electrolysis of nitric acid in simulated wastewater changes. As the electrolysis time increases, the nitrate nitrogen content decreases significantly, the nitrite nitrogen content is almost 0, and the ammonia nitrogen content increases significantly. When the continuous electrolysis time reaches 6 hours, the nitrate nitrogen content is less than 10ppm, reaching the standard for nitrate nitrogen content in drinking water. The above results show that the tungsten-doped cobalt-based dynamic catalyst exhibits excellent electrocatalytic nitric acid reduction to ammonia production performance, and has good application value in the fields of wastewater denitrification and clean ammonia production.
[0080] Example 4
[0081] A method for preparing a chromium-doped cobalt-based dynamic catalyst comprises the following steps:
[0082] S1. Preparation of cobalt-based metal organic framework supported by cobalt foam:
[0083] The foamed cobalt was ultrasonically treated in a hydrochloric acid solution to remove surface oxides;
[0084] A solution of dimethylimidazole and cobalt nitrate solution in a molar ratio of 4:1 is mixed, and then the surface pretreated cobalt foam support is immersed in the mixed solution, and then rinsed with deionized water for 4 times after standing for 25 hours, and then vacuum dried for 48 hours to obtain a cobalt-based metal organic framework supported by the cobalt foam;
[0085] S2. Preparation of chromium-doped cobalt-based metal organic frameworks
[0086] Prepare 10 mM sodium chromate solution
[0087] The cobalt-based metal-organic framework loaded with cobalt foam prepared in S1 is placed in a precursor metal solution for ion exchange reaction. After stirring for 1 hour, the metal ions in the precursor metal solution partially replace the cobalt ions to obtain a chromium-doped cobalt-based metal-organic framework loaded with cobalt foam; the mass fraction of chromium ions in the chromium-ion-doped cobalt-based metal-organic framework is 6wt%.
[0088] S3. The chromium-doped cobalt-based metal organic framework supported by the cobalt foam prepared in step S2 is placed in a tubular furnace, a mixed gas of argon and hydrogen as a protective gas is introduced, and calcined at 600° C. for 0.5 hour to obtain a chromium-doped cobalt oxide / metal cobalt composite material catalyst supported by the cobalt foam.
[0089] S4. Reconstruction of chromium-doped cobalt oxide / metallic cobalt composite catalyst supported on cobalt foam
[0090] At a reduction potential of 0.7 V and a concentration of 0.01 M nitrate ions (from sodium nitrate), the catalyst undergoes dynamic reconstruction to form a chromium-doped cobalt-based dynamic catalyst.
[0091] Example 5
[0092] A method for preparing a molybdenum-doped cobalt-based dynamic catalyst comprises the following steps:
[0093] S1. Preparation of cobalt-based metal organic framework supported by foam iron:
[0094] The foamed iron was ultrasonically treated in a hydrochloric acid solution to remove surface oxides;
[0095] A solution of dimethylimidazole and cobalt nitrate solution in a molar ratio of 16:1 was mixed, and the surface pretreated foam iron carrier was immersed in the mixed solution, and then rinsed with deionized water twice after standing for 5 hours, and then vacuum dried for 12 hours to obtain a cobalt-based metal organic framework supported by the foam iron;
[0096] S2. Preparation of Mo-doped Co-based Metal-Organic Frameworks
[0097] Prepare a 2 mM sodium molybdate solution;
[0098] The cobalt-based metal-organic framework loaded with the foam iron prepared in S1 is placed in a precursor metal solution for an ion exchange reaction. After stirring for 5 hours, the metal ions in the precursor metal solution partially replace the cobalt ions to obtain a molybdenum-doped cobalt-based metal-organic framework loaded with the foam iron; the mass fraction of molybdenum ions in the molybdenum-doped cobalt-based metal-organic framework is 15%.
[0099] S3. The molybdenum-doped cobalt-based metal organic framework supported by the foam iron prepared in step S2 is placed in a tubular furnace, a mixed gas of argon and hydrogen as a protective gas is introduced, and calcined at 400° C. for 2 hours to obtain a molybdenum-doped cobalt oxide / metal cobalt composite material catalyst supported by the foam iron.
[0100] S4. Reconstruction of Mo-doped Cobalt Oxide / Metallic Cobalt Composite Catalyst Supported by Iron Foam
[0101] At a reduction potential of -0.1 V and a nitrate ion concentration of 0.5 M (from lithium nitrate), the catalyst undergoes dynamic reconstruction to form a molybdenum-doped cobalt-based dynamic catalyst.
[0102] Example 6
[0103] A method for preparing a tungsten-doped cobalt-based dynamic catalyst comprises the following steps:
[0104] S1. Preparation of cobalt-based metal organic framework supported by nickel foam:
[0105] The nickel foam was ultrasonically treated in a hydrochloric acid solution to remove surface oxides;
[0106] A solution of dimethylimidazole and cobalt nitrate solution in a molar ratio of 16:1 was mixed, and the surface pretreated nickel foam support was immersed in the mixed solution, and then rinsed with deionized water twice after standing for 5 hours, and then vacuum dried for 12 hours to obtain a cobalt-based metal organic framework supported by nickel foam;
[0107] S2. Preparation of Tungsten-doped Cobalt-based Metal-Organic Frameworks
[0108] Prepare a 2 mM sodium tungstate solution;
[0109] The cobalt-based metal-organic framework loaded with nickel foam prepared in S1 is placed in a precursor metal solution for an ion exchange reaction. After stirring for 5 hours, the metal ions in the precursor metal solution partially replace the cobalt ions to obtain a tungsten-doped cobalt-based metal-organic framework loaded with nickel foam; the mass fraction of molybdenum ions in the tungsten-doped cobalt-based metal-organic framework is 16%.
[0110] S3. The tungsten-doped cobalt-based metal organic framework supported by nickel foam prepared in step S2 is placed in a tubular furnace, a mixed gas of argon and hydrogen as protective gas is introduced, and calcined at 400° C. for 2 hours to obtain a tungsten-doped cobalt oxide / metal cobalt composite material catalyst supported by nickel foam.
[0111] S4. Reconstruction of nickel foam-supported tungsten-doped cobalt oxide / metallic cobalt composite catalyst
[0112] At a reduction potential of -0.1 V and a nitrate ion concentration of 0.5 M (from lithium nitrate), the catalyst undergoes dynamic reconstruction to form a tungsten-doped cobalt-based dynamic catalyst.
[0113] Example 7
[0114] An application of the metal-doped cobalt-based dynamic catalyst in the electro-synthesis of ammonia reaction is specifically:
[0115] The electro-synthetic ammonia reaction uses an H-type electrolyzer, where the cathode chamber and the anode chamber are separated by an anion exchange membrane;
[0116] A standard three-electrode system was used, with the metal-doped cobalt-based catalyst as the working electrode, the Hg / HgO electrode as the reference electrode, and the platinum sheet as the counter electrode;
[0117] The electro-synthetic ammonia reaction uses an H-type electrolytic cell, and the cathode chamber and the anode chamber are separated by an anion exchange membrane. A standard three-electrode system is used, with a metal-doped cobalt-based catalyst as the working electrode, an Hg / HgO electrode as the reference electrode, and a platinum sheet as the counter electrode. The cathode chamber electrolyte is a mixed solution of 1M KOH and a certain concentration of nitrate (the nitrate can be potassium nitrate, sodium nitrate, lithium nitrate, with a concentration of 0.01-0.5M), and the anode chamber electrolyte is 1M KOH. The reaction conditions are to conduct a constant potential test in the voltage range of -0.1V to -0.7V for 1 hour, the temperature is room temperature, and the nitrate in the cathode chamber is reduced to produce ammonia. The ammonia production rate at a voltage of -0.7V is 58.92mg h -1 cm -2 .
[0118] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a metal-doped cobalt-based dynamic catalyst, characterized in that: The steps include: S1. Preparation of cobalt-based metal organic framework supported by nickel foam: Mixing dimethylimidazole and cobalt nitrate solution, then immersing the surface pretreated foam metal support in the mixed solution, standing for 5 to 25 hours, rinsing, and then vacuum drying for 12 to 48 hours to obtain a foam metal-supported cobalt-based metal organic framework; S2. Preparation of metal-doped cobalt-based metal-organic frameworks The cobalt-based metal organic framework supported by the metal foam prepared in step S1 is placed in a precursor metal solution to undergo an ion exchange reaction, and stirred for 1 to 5 hours, so that the metal ions in the precursor metal solution partially replace the cobalt ions to obtain a metal-doped cobalt-based metal organic framework supported by the metal foam; S3, placing the metal-doped cobalt-based metal organic framework supported by the metal foam prepared in step S2 in a tube furnace, introducing a protective gas, and calcining at a temperature of 400 to 600° C. for 0.5 to 2 hours to obtain a metal-doped cobalt oxide / metal cobalt composite material catalyst supported by the metal foam; S4. Reconstruction of metal-doped cobalt oxide / metallic cobalt composite catalyst supported by metal foam At a reduction potential of -0.1V to -0.7V and a nitrate ion concentration of 0.01 to 0.5M, the catalyst undergoes dynamic reconstruction to form a metal-doped cobalt-based dynamic catalyst.
2. The method for preparing the chromium-doped cobalt-based dynamic catalyst according to claim 1, characterized in that: The foam metal is foam nickel, foam cobalt or foam iron, and the pore diameter of the foam metal is 0.2-0.6 mm, preferably 0.4 mm. In the step S1, the molar ratio of dimethylimidazole to the cobalt nitrate solution is 4:1 to 16:
1.
3. The method for preparing the metal-doped cobalt-based dynamic catalyst according to claim 1, characterized in that: The method for pretreating the surface of the foam metal carrier is to ultrasonically treat the foam metal carrier in a hydrochloric acid solution to remove surface oxides.
4. The method for preparing the metal-doped cobalt-based dynamic catalyst according to claim 1, characterized in that: The rinsing is performed by rinsing with deionized water 2-4 times.
5. The method for preparing the metal-doped cobalt-based dynamic catalyst according to claim 1, characterized in that: The precursor metal solution is one of sodium chromate, sodium molybdate or sodium tungstate solution.
6. The method for preparing the metal-doped cobalt-based dynamic catalyst according to claim 5, characterized in that: The concentration of the precursor metal solution is 2-10 mM, and the mass fraction of metal ions in the metal-doped cobalt-based metal organic framework is 6-16 wt.%.
7. The method for preparing the metal-doped cobalt-based dynamic catalyst according to claim 1, characterized in that: The protective gas introduced in step S3 is a mixed gas of argon and hydrogen.
8. The method for preparing the metal-doped cobalt-based dynamic catalyst according to claim 1, characterized in that: In step S4, the nitrate ions come from one of potassium nitrate, sodium nitrate or lithium nitrate or a mixture of several nitrates thereof.
9. A metal-doped cobalt-based dynamic catalyst prepared by the method according to any one of claims 1 to 8.
10. Use of the metal-doped cobalt-based dynamic catalyst according to claim 9 in an electro-synthesis of ammonia reaction.
Citation Information
Cited By
Platinum-cobalt hydroxide composite material with cobalt vacancy and preparation method and application thereof
CN121740988A